ナンキョク エットウ カンソク タイイン ノ モウハツ ビリョウ ゲンソ ノ ヘンドウ - 狐塚, 寛; コズカ, ヒロシ; 神田, 征夫; カンダ, ユキオ; Kozuka, Hiroshi; Kanda, Yukio (国立極地研究所, 1977)
P(論文) 第13次および第15次南極越冬観測隊員の毛髪中の微量元素の変動を放射化分析によりしらべ,つぎのような結果を得た.1)水銀,金,銅,亜鉛,ヒ素の含有量が,南極滞在により減少する傾向が観察された.2)水銀の変動が最も特徴的であり,帰国時に最低値を示して,含有量の集中化(没個性化)の傾向がみられ,帰国後含有量がふたたび上昇,分散した.3)水銀濃度は当初平均7 ppmから帰国時平均4 ppmまで減少したが,この減少のうち1 ppm弱は外界汚染によるもので,2 ppm強は内因性の因子によると考えられる.4)アンチモンでは外界汚染の影響で,含有量が著しく高くなる時期がみられた.この原因は化石燃料からの汚染で,時期は乗船生活時に一致した. The concentrations of trace elements, Hg, Au, Cu, Zn, Sb, As and Br, in the hairs collected from the members of the wintering parties of the 13th and 15th Japanese Antarctic Research Expedition were determined by neutron activation analysis, and the variations of their concentrations during the stay in Antarctica were discussed. The results are as follows : 1) The contents of Hg, Au, Zn and As showed a decreasing trend during the stay in Antarctica. 2) The mercury content showed characteristic variation. Its average concentration and standard deviation decreased from 7.0 ppm to 4.2 ppm and from l.8 to 0.6 ppm respectively at the end of the stay in Antarctica. And its concentration increased again and scattered over a wide range after the return to Japan. 3) The concentration of mercury in the hair reflects both metabolic processes and external contamination. From the results obtained in this work, then, the contributions to the decrease of mercury during the stay in Antarctica were estimated to be 2 ppm for metabolic processes and 1 ppm for external contamination, respectively. 4) The hairs collected on board the icebreaker FUJI showed extremely high concentrations of antimony, indicating the environmental pollution on the icebreaker caused by fuel combustion. departmental bulletin paper